INQUIRY-BASED LEARNING (IBL) IN MATHEMATICS LESSONS (American Journal of Interdisciplinary Research and Development, 2024)
Developing higher-level thinking skills in mathematics lessons is crucial for promoting deeper understanding, problem-solving abilities, and critical thinking. In this article, I will provide some effective methods for fostering higher-level thinking in mathematics lessons.